Travellers’ diarrhoea among tourists in Pakistan - Abdul Thawwab Ishaque; Abdul Raheem Rizvie; Muhammed Ifham Imtiyas (Journal of the Pakistan Medical Association, 2024)
Madam, Travellers’ diarrhoea (TD) emerges as a significant health concern, especially within the South Asian region, which reports the highest Reporting Rate Ratios (RRR)1. Making things even worse, the prolonged summer season in the region amplifies the frequency of reported TD cases, exacerbating the overall scenario2. Notably, travellers to low-income countries exhibit a RRR 150.9 times higher than travellers to high income countries1. Pakistan is no exception, experiencing many TD cases and potential complications among tourists. However, the recent surge in popularity witnessed over 960 million tourists engaging in international travel during 2022, which paves the path for a rise in TD incidence3. Existing prevention and management approaches are constrained and primarily reliant on individual understanding and behaviours. Although travel advisories offer fundamental precautions, a dearth of all-encompassing guidance adapted to the distinct hurdles tourists encounter persists. Furthermore, Pakistan’s scarcity of resources positions it as the 3rd ranked country worldwide facing water shortage and sanitation challenges. Consequently, numerous travellers find themselves inadequately prepared to confront these risks. It becomes apparent that a more methodical and precise strategy is imperative to educate and empower tourists, offering them pragmatic tactics to diminish their vulnerability to TD. Governments, tourism boards, and international organisations should collaborate on culturally tailored education about TD and prevention methods. This can be delivered through workshops, online resources, and campaigns, empowering travellers to make informed decisions. Secure dining areas with hygiene certifications adhering to food safety standards, which should be continuously monitored by the Pakistan Standards and Quality Control Authority (PSQCA) is required to reduce health risks and improve travel experiences. Using mobile apps to empower travellers with informed choices, preventing hazard navigation related to hygiene, quality, pathogens such as Escherichia coli, Campylobacter jejuni etc. and high-risk assessment will provide a safer environment for foreigners. Continuous research should be promoted to manage strategies for evolving challenges and to find cheap and sustainable alternatives. Providing arrival information will equip travellers with prevention and management strategies for self-care. Multimedia campaigns in various languages should be initiated to educate communities and tourists, fostering hygiene commitment for safer travels. Encouraging tourists to get travel vaccinations will reduce the risk of TD for visitors in Pakistan. In conclusion, by implementing these strategies, we strive to ensure the well-being of foreigners and contribute to the broader goal of a healthier and safer tourism environment in Pakistan.